Efektivitas Pendaftaran UMKM Rengginang di Google Maps sebagai Strategi Penguatan Ekonomi Berbasis Teknologi: (Studi Kasus Desa Pahang, Talawi, Batu Bara) - Endang Suriyani Munthe; Nasya Wahyuni; Syairah Nasution; Imsar Imsar (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effectiveness of Rengginang MSME registration on Google Maps as a strategy to strengthen the economy in Pahang Village, Babata Village. The background of the research shows that most MSMEs still rely on conventional marketing so that business visibility is relatively low. With a qualitative case study approach, this study explores the experience of the owner of Rengginang Azam MSMEs, Mrs. Siti, who registered her business location on Google Maps. The results of the study show that digitalization through Google Maps has a positive impact in the form of increasing accessibility and reach for customers, especially from outside the village. Location registration allows customers to find more complete information about products and locations, increasing the number of visits to the store. The real impact felt is an increase in sales and profits without additional promotional costs. This study concludes that the use of Google Maps as a digital promotional medium is an effective strategy in strengthening the competitiveness of MSMEs in the digital era. In addition, this finding confirms the importance of digital literacy for MSME actors to utilize technology as a means of business development and strengthening the local economy.